Effect of kayak ergometer loading on upper limb recruitment and kinematics - Fleming, N.; Donne, B.; Fletcher, D. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction Altered upper limb muscle recruitment patterns were recently reported comparing on-ergometer and on-water kayaking (Fleming et al., 2010, 2012); however, precise mechanisms underlying EMG changes remain to be elucidated. This study assessed the effect of altered ergometer recoil force on upper limb recruitment patterns and kinematics during the kayak stroke via EMG and 3D kinematic analysis. Methods: Male flat-water kayakers (n=10, mean ± SD; age 21±3yr, height 1.80±0.06m, body mass 74.6±5.8kg) performed 4 by 1 min on-ergometer exercise bouts at a load equivalent to 85%VO2max at varying elastic recoil tensions ranging from 0% shortened (T1) up to 30% shortened (T4). Trials were randomised to eliminate possible effect of tension order on kinematics or EMG activity. During exercise, surface EMG data (Mega ME6000) were recorded from Anterior Deltoid (AD), Triceps Brachii (TB) and Latissimus Dorsi (LD). In addition, stroke force (instrumented paddle) and 3D kinematic (CODA) data were recorded. EMG data from 10 consecutive stroke cycles in the latter stages of each trial were amplitude processed via root mean squaring and normalised relative to pre-trial isometric MVC. Stroke force and 3D kinematic data recorded from wrist, elbow, shoulder and scapular markers were assessed over the same time frame. Data were analysed using repeated measures ANOVA and detected differences quantified using post-hoc Tukey tests (P<0.05). Results: While stationary recoil forces significantly increased across investigated tensions (20±4 to 45±8 N, P<0.001), no significant differences were detected in assessed stroke force variables. Increasing tension induced significantly higher normalised AD rmsEMG activity in the 70 to 90% stages of the stroke cycle (T4 vs. T1; 18.1±12.0 vs. 10.6±5.3 %, P<0.05; 37.6±16.2 vs. 22.7±11.0 %, P<0.001 and 26.3±10.1 vs. 15.6±8.9 %, P<0.001 at 70, 80 and 90 %, respectively). No significant differences were observed across tension in TB or LD. A detailed 3D kinematic analysis revealed that overhead arm movements accounted for 58±10% of the cycle. At stroke cycle onset mean elbow angle was 144±10° and maximal angle (151±7°) occurred at 78±10 % of stroke cycle. Overall upper arm kinematic markers moved horizontally forward as recoil tension increased. No significant change in wrist marker elevation was observed. Elbow and shoulder marker elevations significantly increased during the 70 and 80% intervals of the cycle (P<0.05). Discussion: Data suggested that kayakers maintained normal hand position during the cycle via additional AD recruitment despite ergometer induced recoil forces being applied to the upper arm.